Routine Screening for Callosal Dysgenesis in the Second Trimester Is Achievable With Intensive Training. (1st March 2016) - Lavender, Ilona; Coombs, Peter R.; Van Haltren, Keith; Robinson, Alice J.
Abstract : Objectives: The purpose of this study was to determine whether routine direct visualization of the corpus callosum is achievable during second‐trimester sonography when performed by a large group of sonographers in a general second‐trimester sonographic screening program. The secondary aim was to determine the time taken to obtain a sagittal corpus callosum image. Methods: We conducted a retrospective cohort study of visualization of the corpus callosum before and after intensive training. Images from 150 consecutive second‐trimester scans were reviewed before and after training to evaluate the image quality of the corpus callosum. Results: A total of 300 cases were evaluated before and after training. There was a significant increase in the rate of complete visualization of the corpus callosum after intensive training ( P < .0001). Before training 35 of 150 cases (23%) had complete visualization of the corpus callosum versus 107 of 150 (71%) after training. The mean time to perform the corpus callosum views was 53.4 seconds before training compared to 56.2 seconds after training. Conclusions: Assessing the corpus callosum in the sagittal view is difficult and requires appropriate training and patience; however, this view is feasible without adding substantial time to the examination and provides additional information during a routine second‐trimester morphologic scan.